1986
DOI: 10.1002/1097-4679(198603)42:2<369::aid-jclp2270420227>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the WAIS-R for an incarcerated population

Abstract: The factor structure of the Wechsler Adult Intelligence Scale‐Revised (WAIS‐R) for a large sample of incarcerated individuals (N = 234) was investigated. A principal components analysis followed by Varimax rotation identified the familiar Perceptual Organization and Verbal Comprehension factors. Coefficients of congruence between the current factors and those of the WAIS‐R standardization sample indicate a high degree of correspondence. Thus, empirical support was provided for interpretation of WAIS‐R Performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…, prisoners (Faulstich et al, 1986;Faulstich, McAnulty, Carey, & Gresham, 1987), clients referred for neuropsychological assessment (Atkinson, Cyr, Doxey, & Vigna, 1989;Ryan & Schneider, 1986;Warner, Ernst, & Townes, 1986), learning-disabled adults (Blaha, Mandes, & Swisher, 1987), nonpsychiatric, clinic-referred clients (Geary & Whitworth, 1988), and individuals with low IQ (Atkinson & Cyr, 1988). No attempts were reported to extract the one-factor solution from a clinical sample, but in all cases the two-factor solution was extracted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, prisoners (Faulstich et al, 1986;Faulstich, McAnulty, Carey, & Gresham, 1987), clients referred for neuropsychological assessment (Atkinson, Cyr, Doxey, & Vigna, 1989;Ryan & Schneider, 1986;Warner, Ernst, & Townes, 1986), learning-disabled adults (Blaha, Mandes, & Swisher, 1987), nonpsychiatric, clinic-referred clients (Geary & Whitworth, 1988), and individuals with low IQ (Atkinson & Cyr, 1988). No attempts were reported to extract the one-factor solution from a clinical sample, but in all cases the two-factor solution was extracted.…”
mentioning
confidence: 99%
“…In an effort to determine if results were generalizable across populations, a number of clinical samples have also been studied. These include vocational rehabilitation clients (Ryan, Rosenberg, & DeWolfe, 1984), psychiatric patients (Atkinson & Cyr, 1984; Beck, Horwitz, Seidenberg, Parker, & Frank, 1985), medical psychology patients (Beck, Horwitz, Seidenberg, Parker, & Frank, 1985), prisoners (Faulstich et al, 1986; Faulstich, McAnulty, Carey, & Gresham, 1987), clients referred for neuropsychological assessment (Atkinson, Cyr, Doxey, & Vigna, 1989; Ryan & Schneider, 1986; Warner, Ernst, & Townes, 1986), learning-disabled adults (Blaha, Mandes, & Swisher, 1987), nonpsychiatric, clinic-referred clients (Geary & Whitworth, 1988), and individuals with low IQ (Atkinson & Cyr, 1988). No attempts were reported to extract the one-factor solution from a clinical sample, but in all cases the two-factor solution was extracted.…”
mentioning
confidence: 99%
“…The continued investigation of WAIS-R factor structures with a variety of samples is an essential step in furthering knowledge of human intelligence. To date, investigators have reported on normal subjects between 16 and 74 years of age (Blaha & Wallbrown, 1982; Gutkin, Reynolds, & Galvin, 1984; Naglieri & Kaufman, 1983; O'Grady, 1983; Parker, 1983; Silverstein, 1982), incarcerated criminals (Faulstich et al, 1986), vocational rehabilitation clients (Fraboni, Saltstone, Baines, & Cooper, 1988; Ryan, Rosenberg, & DeWolfe, 1984), and patients with medical, psychiatric, and/or neurological disorders (Atkinson & Cyr, 1984; Beck, Horwitz, Seidenberg, Parker, & Frank, 1985; Bornstein, Drake, & Pakalnis, 1988; Ryan, Prifitera, & Rosenberg, 1983; Ryan, Rosenberg, & Heilbronner, 1984; Ryan & Schneider, 1986). Unfortunately, there have been no studies of persons 75 years of age or older.…”
mentioning
confidence: 99%